Variation of thermal conductivity of DPPC lipid bilayer membranes around the phase transition temperature - Youssefian, Sina (J R Soc Interface, 2017)
Given their amphiphilic nature and chemical structure, phospholipids exhibit a strong thermotropic and lyotropic phase behaviour in an aqueous environment. Around the phase transition temperature, phospholipids transform from a gel-like state to a fluid crystalline structure. In this transition, many key characteristics of the lipid bilayers such as structure and thermal properties alter. In this study, we employed atomistic simulation techniques to study the structure and underlying mechanisms of heat transfer in dipalmitoylphosphatidylcholine (DPPC) lipid bilayers around the fluid–gel phase transformation. To investigate this phenomenon, we performed non-equilibrium molecular dynamics simulations for a range of different temperature gradients. The results show that the thermal properties of the DPPC bilayer are highly dependent on the temperature gradient. Higher temperature gradients cause an increase in the thermal conductivity of the DPPC lipid bilayer. We also found that the thermal conductivity of DPPC is lowest at the transition temperature whereby one lipid leaflet is in the gel phase and the other is in the liquid crystalline phase. This is essentially related to a growth in thermal resistance between the two leaflets of lipid at the transition temperature. These results provide significant new insights into developing new thermal insulation for engineering applications.